Caracterización epidemiológica, clínica y de laboratorio de esporotricosis en pacientes de un hospital de tercer nivel en Lima-Perú, entre los años 1991 y 2014 - James A Oyarce; Coralith García; Jorge Alave; Beatriz Bustamante (My University, 2016)
BACKGROUND: Sporothricosis is endemic in numerous Latin American countries and the rest of the world. In Peru is concentrated in regions with warm and humid climate being little known in the rest of the country. AIM: To describe the epidemiological, clinical and laboratory characteristics of patients diagnosed of sporotrichosis in a tertiary-care level hospital in Lima, Peru from 1991 to 2014. METHODS: This was a retrospective, case series. RESULTS: Ninety four patients were involved; most of them were male adults. This condition was acquired more frequently in Cajamarca, Apurímac, and Amazonas. Fixed and lymphocutaneous form were the most frequent forms of presentation in adults and were mostly distributed in upper limbs. Lesions located in head and neck were most frequent in children. Comorbidities were present in 15% of patients and were more frequent in those who presented disseminated cutaneous form. Seventy eight percent of cultures from skin lesions were positive within 7 days. The time to positivity of cultures was longer if the sample came from skin biopsies than skin scraping or skin aspiration. CONCLUSIONS: Most cases of sporotrichosis were acquired in areas of extreme poverty in Peru. The clinical, epidemiological and laboratory findings were similar to those reported elsewhere. The time to positivity of cultures varies based on the type of skin sample. This finding needs to be further evaluated in studies with an increased number of cases.
Keywords: Sporotrichosis; Medicine; Epidemiology; Tropical medicine; Head and neck; Pediatrics; Demography; Dermatology; Surgery; Internal medicine; Pathology; Sociology; Sporotrichosis; Medicine; Epidemiology; Tropical medicine; Head and neck; Pediatrics; Demography; Dermatology; Surgery; Internal medicine; Pathology; Adolescent; Adolescent; Adolescent; Adult; Adult; Adult; Aged; Aged; Aged; Aged, 80 and over; Aged, 80 and over; Aged, 80 and over; Antifungal Agents therapeutic use; Antifungal Agents therapeutic use; Antifungal Agents therapeutic use; Biopsy; Biopsy; Biopsy; Child; Child; Child; Child, Preschool; Child, Preschool; Child, Preschool; Female; Female; Female; Humans; Humans; Humans; Male; Male; Male; Middle Aged; Middle Aged; Middle Aged; Peru epidemiology; Peru epidemiology; Peru epidemiology; Poverty Areas; Poverty Areas; Poverty Areas; Retrospective Studies; Retrospective Studies; Retrospective Studies; Socioeconomic Factors; Socioeconomic Factors; Socioeconomic Factors; Sporotrichosis drug therapy; Sporotrichosis drug therapy; Sporotrichosis drug therapy; Sporotrichosis epidemiology; Sporotrichosis epidemiology; Sporotrichosis epidemiology; Sporotrichosis pathology; Sporotrichosis pathology; Sporotrichosis pathology; Sporothrix isolation & purification; Sporothrix isolation & purification; Sporothrix isolation & purification; Time Factors; Time Factors; Time Factors; Young Adult; Young Adult; Young Adult; Tertiary Care Centers statistics & numerical data; Tertiary Care Centers statistics & numerical data; Tertiary Care Centers statistics & numerical data; Health Sciences Medicine Epidemiology Fungal Infections and Studies; Health Sciences Medicine Epidemiology Nail Diseases and Treatments; Physical Sciences Environmental Science Health, Toxicology and Mutagenesis Insects and Parasite Interactions